2015
DOI: 10.3390/nu7042930
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microbial Amino Acid Metabolism in Host Metabolism

Abstract: Disruptions in gut microbiota composition and function are increasingly implicated in the pathogenesis of obesity, insulin resistance, and type 2 diabetes mellitus. The functional output of the gut microbiota, including short-chain fatty acids and amino acids, are thought to be important modulators underlying the development of these disorders. Gut bacteria can alter the bioavailability of amino acids by utilization of several amino acids originating from both alimentary and endogenous proteins. In turn, gut b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
543
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 688 publications
(573 citation statements)
references
References 108 publications
23
543
0
7
Order By: Relevance
“…In particular, the functional output of the gut microbiota, including short-chain fatty acids (SCFAs), amino acids, and secondary biliary acids, is thought to modulate the pathogenesis of obesity (146). The known roles of some metabolites in immune cell function support their possible involvement in modulating alloimmunity.…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nmentioning
confidence: 99%
“…In particular, the functional output of the gut microbiota, including short-chain fatty acids (SCFAs), amino acids, and secondary biliary acids, is thought to modulate the pathogenesis of obesity (146). The known roles of some metabolites in immune cell function support their possible involvement in modulating alloimmunity.…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nmentioning
confidence: 99%
“…Mostly intercellular lipid intermediates, sphingolipids and bile acid intermediates are associated to obesity [77]. Microbial metabolism produces SCFAs from host amino acids, and changes in plasma levels of some amino acids are associated with T2DM [79], particularly aromatic amino acids. In a Qatari study, predictors of T2DM were identified in different body fluids, saliva, plasma, and urine, at different timescales of glycemic control, revealing a connection between metabolites across the body fluids and a specific association of metabolites with the timescales of glycemic control [44].…”
Section: Nutrigenomic Approaches To Obesitymentioning
confidence: 99%
“…Bacteria of the rumen may be incorporated straight into amino acids and peptides from the diet [5]. Consequently, there is need to consider the proportion of peptides and amino acids in dairy cow rations.…”
Section: Introductionmentioning
confidence: 99%